EU, Eastern Europe and Values Imperialism - S. White (Vestnik MGIMO-Universiteta)
This paper proposes an idea of'values imperialism'as a helpful way of conceptualising the relationship between the EU and the states that came within its sphere of influence after the end of the Cold War, particularly its 'neighbours' in Eastern Europe. Values imperialism places its emphasis on the 'superstructure', including norms, laws and social practices. EU larger objective was that the assumptions about government and ownership that were favoured by the dominant powers (EU and the West in the broad term) should be absorbed and recapitulated by those countries that were subordinate. The broad framework ofsubordination was established by the Partnership and Cooperation Agreements that began to be concluded from 1994 onwards. Patterns of'values imperialism'could also be discovered in the EU Common Strategies on Russia and Ukraine that were adopted in 1999. Article also points out several cases when the EU intervened directly in the domestic affairs of the Eastern Europe countries in a manner that was not always compatible with the provisions on state sovereignty: a 'European Instrument for Democracy and Human Rights', launched in 2006, interventions ofEU representatives in the work of local courts and organisation of exit polls, which could be used to discredit the official election results and in this way to undermine the position of local governments. Finally, the author concludes that the EU used 'values imperialism'practices in order to extend its influence, particularly in the Eastern Europe.